When things get too much. Issue 9 (21st December 2020) - McCurry, Robyn
Abstract: Registered veterinary nurses (RVNs) are highly trained and skilled individuals who on a daily basis provide compassion and care to animals and clients. Whilst always caring for others, RVNs can start to experience stress, leading to more serious implications such as burn out and compassion fatigue. Monitoring for stress, burnout and compassion fatigue is important and having coping mechanisms in place can make a significant difference. This article will explore these terms and how to incorporate coping strategies into everyday life.